2020
DOI: 10.5603/gp.2020.0017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and prognostic factors of concurrent chemoradiotherapy in patients with stage Ib3 and IIa2 cervical cancer

Abstract: Objectives: We investigated the efficacy, side effects, and prognostic factors of concurrent chemoradiotherapy for patients with stage Ib3-IIa2 cervical cancer. Material and methods: We conducted a retrospective analysis of clinicopathologic data from 73 patients with stage Ib3-IIa2 cervical cancer who received concurrent chemoradiotherapy from January 2008 to December 2013 in our hospital. Overall response and disease control rates were used to evaluate short-term outcomes; the 3-year and 5-year disease-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the course of radiotherapy, different radiation doses for corresponding target areas may protect normal tissues and increase the local dose of tumors. 16 A study by Liu et al 17 concluded that the IMRT technique boasted of shortening the total treatment time and improving tumor control rate and survival rate without increasing the radiotoxicity of normal tissues. Adverse events frequently associated with this technique included nausea, vomiting, alopecia, neutropenia, and leukopenia, most of which were grade one or two in intensity, with few serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of radiotherapy, different radiation doses for corresponding target areas may protect normal tissues and increase the local dose of tumors. 16 A study by Liu et al 17 concluded that the IMRT technique boasted of shortening the total treatment time and improving tumor control rate and survival rate without increasing the radiotoxicity of normal tissues. Adverse events frequently associated with this technique included nausea, vomiting, alopecia, neutropenia, and leukopenia, most of which were grade one or two in intensity, with few serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…For local middle-stage and advanced tumors, due to the large tumor load, poor differentiation, wide range of local invasion, and high proportion of hypoxic cells, the 5-yearPFS rate is approximately 67%. In addition, 33% of patients experience local recurrence and/or distant metastasis within two years[ 10 - 13 ]. One of the key factors leading to local tumor recurrence after chemotherapy and radiotherapy is the increased expression of VEGF induced by radiotherapy, which results in increased local neovascularization, radiation resistance and possible distant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research results, the 2-years PFS of LACC patients in RS group (group A) and CCRT group (group B) were respectively estimated at 85% and 80% [ 18 19 20 21 22 23 ]. Considering the limited amounts of CCRT patients in the leading and participating centers, influenced by the Chinese culture, we allocate patients into these 2 groups at a 3:1 ratio.…”
Section: Methodsmentioning
confidence: 99%